THE EFFECT OF COMPANY SIZE, AUDIT COMMITTEE, BOARD OF DIRECTORS AND BOARD OF COMMISSIONERS ON COMPANY VALUE - Hana Hanifah; Gema Ika Sari; Dini Awaliyah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Finding out whether the Board of Directors, Board of Commissioners, Audit Committee, and Company Size significantly impact Firm Value in Primary Consumer Goods (Non-Cyclical Consumption) Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 Period is the main objective of this research. As supplementary data, this study uses financial data available on the Indonesia Stock Exchange website (www.idx.co.id). As a result of using purposeful sampling, 77 core consumer goods businesses were included in the sample. Multicollinearity, autocorrelation, normality, and heteroscedasticity tests were among the data-preparation tests. The method used to analyse the data included multiple linear regression, correlation, coefficient of determination, partial t-testing, and simultaneous F-tests. According to the study's findings, there is a partial impact of the Board of Directors variable on Company Value, a partial impact of the Board of Commissioners variable on Company Value, an impact of the Audit Committee variable on Company Value, an impact of Company Size on Company Value, and a combined impact of the Board of Directors, the Board of Commissioners, company size, and audit committee on Company Value.